Contributions from theories of organisational justice: A narrative and critical literature review - Omar RAJÂA; Hajar MORRO (International Journal of Scientific Research and Innovative Studies, 2026)
Organisational justice is a prolific field of research in management sciences and work psychology. This article provides a narrative and critical review of the literature on the theoretical and empirical contributions of this multidimensional construct. Drawing on a body of work selected through a transparent protocol (including seminal meta-analyses, empirical studies conducted across diverse geographical and sectoral contexts (Morocco, Japan, Hong Kong, Ghana, Tunisia, Turkey), and foundational integrative models), we examine the conceptual foundations of organisational justice, the explanatory mechanisms identified (social exchange theory, affective perspective, social identity), the main attitudinal and behavioural consequences documented, and contemporary extensions of the concept, particularly in the context of digital transformation. The cross-sectional analysis reveals consensus on the validity of the four-dimensional model and the significant effects of perceived justice on commitment, satisfaction, and turnover intention, whilst identifying recurring methodological limitations and persistent theoretical gaps. An integrative conceptual framework is proposed, articulating the antecedents, dimensions, mediating mechanisms, and consequences of organisational justice. Priority directions for future research are formulated. Keywords: organisational justice; distributive justice; procedural justice; interactional justice; social exchange; organisational commitment; well-being at work; literature review Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/637